IL‐10 promoter polymorphisms influence susceptibility to aGvHD and are associated with proportions of CD4+FoxP3+ lymphocytes in blood after hematopoietic stem cell transplantation. Issue 6 (December 2013) - Jaskula, E.; Lange, A.; Dlubek, D.; Kyrcz‐Krzemień, S.; Markiewicz, M.; Dzierzak‐Mietla, M.; Jedrzejczak, W. W.; Gronkowska, A.; Nowak, J.; Warzocha, K.; Hellmann, A.; Kowalczyk, J.; et al.
Abstract Four hundred and ninety‐five patients (390 and 105 grafted from unrelated and sibling (SIB) donors, respectively) and their donors were analyzed for the impact of interleukin‐10 (IL‐10) promoter genotype [rs18000896 (−1082 G/A), rs18000871 (−819 C/T) and rs18000872 (−592 C/A)] on the outcome of hematopoietic stem cell transplantation (HSCT). Patients having ACC haplotype were at a lower risk of acute graft versus host disease (aGvHD, grade > I) if transplanted from human leukocyte antigen (HLA) well‐matched (10/10) unrelated donors (20/135 vs 39/117, P < 0.001, Pcorr = 0.002), which was not seen if patients were transplanted from either sibling (SIB) or poorly matched (<10/10) unrelated donors (MUD). In addition, GCC haplotype positive recipients of unrelated donor transplants tended to be more susceptible to aGvHD (68/199 vs 39/169, P = 0.019, Pcorr = 0.057). Multivariate logistic regression analysis in the MUD transplanted group showed that donor–recipient human leukocyte antigen (HLA) mismatch [odds ratio (OR) = 3.937, P = 0.001] and a lack of ACC haplotype in recipients (OR = 0.417, P = 0.013) played a significant role as independent risk factors of aGvHD grade > I. ACC carriers had higher proportions of FoxP3+ lymphocytes gated in CD4+ lymphocytes as compared with patients with other IL‐10 haplotypes. It was seen at the time of hematological recovery (mean ± SEM: 3.80 ± 0.91% vs 2.06 ± 0.98%, P = 0.012) and 2 weeks later (5.32 ± 0.87% vs 2.50 ± 0.83%, P = 0.013); −592 C/A polymorphism was separately analyzed and it was found that AA homozygotes tended to have a higher incidence of aGvHD (8/15 vs 116/456, P = 0.034) and low proportions of FoxP3 CD4+ lymphocytes in blood (0.43 ± 0.22% vs 4.32 ± 0.71%, P = 0.051) measured 2 weeks after hematological recovery. Functional IL‐10 polymorphism associated features influenced the risk of aGvHD with a positive effect of ACC on the pool of Treg in blood.